Undifferentiated (Anaplastic) Carcinoma of the Pancreas with Osteoclast-Like Giant Cells Showing Various Degree of Pancreas Duct Involvement. A Case Report and Literature Review - Maksymov, Vlad; Khalifa, Mahmoud A; Bussey, Angela; Carter, Beverly; Hogan, Michael (JOP. Journal of the Pancreas, 2011)
Context Undifferentiated (anaplastic) carcinoma of the pancreas with osteoclast-like giant cells is exceedingly rare. The prognosis of undifferentiated carcinoma is worse than that of poorly differentiated ductal adenocarcinoma of the pancreas; however, undifferentiated carcinoma with osteoclast-like giant cells might have a more favorable prognosis. Case report We report the case of undifferentiated carcinoma of the pancreas with osteoclast-like giant cells, showing an intraductal growth pattern with various degree of pancreas duct involvement in the different areas. As a result, we were able to demonstrate the entire spectrum of changes, ranging from the early, minimal intraluminal growth to the partial or complete occlusion of the branches of the main pancreatic duct, and finally invasion and formation of the large necrotic/degenerated cysts. Conclusions Our findings support the epithelial origin of undifferentiated carcinoma of the pancreas with osteoclast-like giant cells. In early stages, the affected pancreatic duct epithelium was intermingled with nonepithelial component and had an immunoprofile distinctive from the epithelial lining of the uninvolved (normal) pancreatic ducts. Distinctive immunoprofile (CK 5/6, p63 and p53 positive) of the epithelial component and p63 and p53 positivity of the nonepithelial component should be explained and further investigated in the similar cases. Our findings support prior assertions that undifferentiated carcinoma of the pancreas with osteoclast-like giant cells may develop from carcinoma in situ within the main pancreatic duct or its branches. Image: Pancreaticoduodenectomy specimen.